JUMPA Vol.3 No.1 Feb 2016 ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI DIVIDEND PAYOUT RATIO (DPR) DI PERUSAHAAN GO PUBLICK YANG TERDAFTAR DI BURSA EFEK INDONESIA SELAIN JASA KEUANGANDENGAN MODEL VECTOR AUTOREGRESIVE PERIODE 2009 -2013: ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI DIVIDEND PAYOUT RATIO (DPR) DI PERUSAHAAN GO PUBLICK YANG TERDAFTAR DI BURSA EFEK INDONESIA SELAIN JASA KEUANGANDENGAN MODEL VECTOR AUTOREGRESIVE PERIODE 2009 -2013 - Zara Tania Rahmadi Sekolah Tinggi Ilmu Ekonomi Y.A.I. Jakarta; Adji Suratman Sekolah Tinggi Ilmu Ekonomi Y.A.I. Jakarta (Sekolah Tinggi Ilmu Ekonomi Y.A.I - Jakarta - Indonesia, 2016)
This research aimed to analyze the influence of factors such as current ratio, debt to asset ratio, debt to equity ratio, return on assets and return on equity of the company dividend policy with vector autoregressive models as a tool of analysis, Sample of this research is the company to go public in addition to the financial services listed in the Indonesia Stock Exchange (BEI) as many as 25 companies were observed for five years (2009-2013).The analytical method used in this research is panel data regression model (a combination of time series and cross section) and vector autoregressive models (VAR) by outlining this research model into several sub-structural. The research results with the VAR model shows that the current ratio, debt to asset ratio, return on assets have a significant influence on the dividend payout ratio and debt to equity ratio, return on equity does not have a significant influence on the dividend payout ratio.so itcan be concluded that this is dueif therate of return on asset sincreased currentm ratio automatically rises and dividend payments can be smoothlypaid outso as to provide symmetry between these variables.